Analysis of Consumer Behavior in Purchasing Decisions at Go Thai Tea Sumedang - Sumiati, Ai; Aulia, Agni; Amelia, Amelia; Apriana, Dedeng; Rohimat, Deden; Noviyanti, Dewi (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
This research investigates various factors that influence consumer behavior when they choose to purchase Go Thai Tea products in Sumedang. Cultural, social, personal and psychological factors are the components studied. Primary data from in-depth interviews, direct observation, and secondary data from literature were used in the exploratory descriptive method in this research. The research results show that several main factors that influence buyers' decisions are local preferences for taste, the influence of social media, recommendations from friends and family, affordable prices, and positive perceptions about product quality and packaging. Customer loyalty increases due to taste innovation, comfortable store atmosphere and effective marketing tactics. It is hoped that this research will help businesses understand consumer behavior and create better marketing strategies in today's